Kerjasama antara Tri Pusat Pendidikan dalam Pembinaan Peserta Didik - Putri, Sabrina Rida (Yayasan Sukma Bangsa, 2023)
This article discusses the importance of collaboration between three educational centers, namely the family, school and community, in fostering students. Multicultural education in Indonesia is a solution to overcome existing diversity, with the aim of advancing the nation. Education has a crucial role in shaping the character of students, but it does not only occur in the formal education system (schools), but also involves the family and community environment. In this study, the library research method was used to analyze literature relevant to the problem under study. The results of the study show that the family, school and community have an important role in children's education. The family as the first environment provides the basis of education, while the school facilitates the development of children. The community environment shapes individual attitudes and values. Cooperation between families, schools and communities is needed in children's education. Parents need to be involved in home education, teachers need to understand children's backgrounds, and the school environment needs to support individual development.